Reproductive outcomes in progesterone-based fixed-time AI protocols in Bos indicus - Madureira, Guilherme (2019)
To improve the knowledge on progesterone (P4)-based hormonal protocols for synchronization of ovulation in Bos indicus, three studies were performed. The first study, consisting of three experiments (two in non-lactating cows, and one in Nelore heifers), were based on daily ultrasound evaluation and blood sampling for circulating P4 at specific times [onset of the protocol (D0) and first prostaglandin F2α (PGF) administration] of P4-based protocols differing in: inducer of the follicle wave emergence; protocol lengths; and ovulation inducer at the end of the protocol. Administration of 16.8 µg of buserelin acetate (GnRH) at the beginning of the protocol was associated with better ovulation rate after D0 (~55%), and higher number of corpus luteum (CL) at PGF. In addition, sometimes GnRH-based protocols were associated to early emergence of the follicle wave (~1.9 d after D0) and/or bigger ovulatory follicle, as well as greater circulating P4 at the time of PGF, especially in females that ovulated after GnRH administration. Nevertheless, protocols based on estradiol benzoate (EB) promoted delayed follicular wave emergence (~2.4 d after D0), but both (GnRH and EB) were associated to satisfactory synchronization rate of follicular wave emergence between D0 and D5 (~92%). In contrast, short protocols (5 d of P4 implant) only with insertion of a P4 implant on D0 were associated to low follicle wave emergence between D0 and D5 (~30%). However, the three strategies mentioned above promoted high ovulation rate at the end of the protocol (~85%), and did not differ in relation to the time of ovulation. The second study, consisting of two experiments (one in Nelore heifers, and the second in Nelore cows), evaluated fertility and some physiological variables of P4-based 7 d protocols beginning with EB (conventional protocol) or GnRH (16.8 µg of buserelin acetate) with adaptations (eCG and PGF on D6, and an additional PGF on D7), and with or without GnRH (8.4 µg) administration at the time of AI. As expected, higher ovulation rate after D0 (~67%) and more CL at PGF were observed in protocols starting with GnRH. Administration of EB at the beginning of the protocol was associated to greater luteolysis rate between D0 and PGF (~33%). At the time of implant withdrawal (D7), GnRH-based protocols induced bigger dominant follicles, and more estrus expression by the time of AI. However, only in heifers it was observed a bigger dominant follicle at the time of AI for GnRH group. Both (GnRH and EB) obtained satisfactory ovulation rate after AI (~92%). In heifers, no treatment effect was observed (EB vs. GnRH on D0, with vs. without GnRH at the time of AI) or interactions on pregnancy/AI (P/AI). However, in cows EB-based protocols obtained great P/AI when GnRH was administered at the time of AI (60.2% vs. 69.5%). In addition, this administration also increased P/AI of cows that did not express estrus during the protocol (no estrus: no GnRH = 48.2% vs. GnRH = 59.1%), although this effect was not observed in heifers. The third study evaluated ovarian dynamics and fertility of Nelore cows submitted to a P4-based 7 d FTAI protocol using 0.5 or 1.0 mg of estradiol cypionate (EC) at the time of implant removal (D7). Although 1.0 mg EC induced a smaller preovulatory follicle and lower ovulation rate after AI in multiparous, the P/AI was similar for both doses in this parity (multiparous: 0.5 mg = 58.4% vs. 1.0 mg = 59.0%). However, primiparous had lower P/AI when receiving 0.5 mg EC (primiparous: 0.5 mg = 30.2% vs. 1.0 mg = 53.6%). Therefore, both studies allowed a more refined knowledge regarding P4-based protocols in Bos indicus, especially on the efficiency of 7 d protocols and the inclusion of GnRH at the start or in the end of this type of synchronization protocol.